Forecasting the Competitiveness of Major Wheat Exporters Amidst the Russia and Ukraine Crisis - Mohamad, Abdul Hayy Haziq; Ab-Rahim, Rossazana (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
Major concerns about the food security involving wheat production emerged when the conflict between Russia and Ukraine worsened because both countries were the main suppliers of wheat to 38 countries. This study aims to explore the competitiveness level of wheat production countries and the future exporters that may lead to global wheat production during the Russia-Ukraine crisis. This study analyzed the comparative advantages of the five largest wheat exporters from 2001 to 2021 using the revealed comparative advantage (RCA) and revealed symmetrical comparative advantage (RSCA) indices to examine the current level of wheat export competitiveness of the five major exporters. This study also predicts the three major wheat-producing countries (excluding Russia and Ukraine) using 83-month observations to forecast the autoregressive integrated moving average in the next six months. The findings disclosed that all major wheat countries were strongly competitive, and the forecast unveiled that Australia is capable to lead the wheat producing countries in the next six months. This evaluation was derived from the ARIMA approach’s forecast, demonstrating Australia to be statistically greater than the USA and Canada.